Cyclodextrins and ternary complexes: technology to improve solubility of poorly soluble drugs - Janisse Crestani de Miranda; Tércio Elyan Azevedo Martins; Francisco Veiga; Humberto Gomes Ferraz (Universidade de São Paulo, 2011)
Cyclodextrins (CDs) are cyclic oligosaccharides composed of D-glucopyranoside units linked by glycosidic bonds. Their main property is the ability to modify the physicochemical and biological characteristics of low-soluble drugs through the formation of drug:CD inclusion complexes. Inclusion complexation requires that host molecules fit completely or partially within the CD cavity. This adjustment is directly related to the physicochemical properties of the guest and host molecules, easy accommodation of guest molecules within the CD cavity, stoichiometry, therapeutic dose, and toxicity. However, dosage forms may achieve a high volume, depending on the amount of CD required. Thus, it is necessary to increase solubilization efficiency in order to use smaller amounts of CD. This can be achieved by adding small amounts of water-soluble polymers to the system. This review addresses aspects related to drug complexation with CDs using water-soluble polymers to optimize the amount of CD used in the formulation in order to increase drug solubility and reduce dosage form volume. Ciclodextrinas (CDs) são oligossacarídeos cíclicos, compostos por unidades D-glicopiranosídicas ligadas entre si por meio de ligações glicosídicas e sua principal propriedade está na capacidade de alterar as características físico-químicas e biológicas de fármacos com baixa solubilidade por meio da formação de complexos de inclusão fármaco:CD. Para a formação dos complexos de inclusão a molécula hospedeira necessita ajustar-se total ou parcialmente no interior da cavidade da CD, onde este ajuste está diretamente ligado a propriedades físico-químicas da molécula hóspede e hospedeira, facilidade de alojamento da molécula hóspede no interior da cavidade da CD, estequiometria, dose terapêutica e toxicidade. No entanto, as formas farmacêuticas podem atingir um elevado volume, em função da quantidade de CD requerida, sendo necessário aumentar sua eficiência de solubilização para que seja possível utilizar menores quantidades das mesmas. Isso pode ser obtido com a inclusão de pequenas quantidades de polímeros hidrossolúveis ao sistema. Nessa revisão, são abordados aspectos relacionados à complexação de fármacos com ciclodextrinas empregando-se polímeros hidrossolúveis para otimização da quantidade de CD utilizada na formulação, com a finalidade de aumentar a solubilidade do fármaco e reduzir o volume das preparações.